ANALISIS MARKETING MIX SYARIAH DALAM MENINGKATKAN JUMLAH PENGUNJUNG TERHADAP OBJEK WISATA DAERAH BENGKULU (STUDI KASUS OBJEK WISATA PULAU KUMAYAN KOTA BENGKULU) - Ilhami, Marda Rido; Hak, Nurul; Sumarni, Yenti (ITB AAS Indonesia Surakarta, 2024)
The purpose of this studi was to describe a marketing mix based on sharia marketing in increasing visitors to the Kumayan Island tourist attraction, Bengkulu City. This research method uses descriptive qualitative. The results of the research concluded that the Kumayan Island tourist attraction has implemented the 7p marketing mix but there are 2 elements that have not been implemented perfectly, namely the place related to distribution which has not involved third parties to collaborate with tourism managers and physical avidence where the physical facilities provided are not yet adequate. from road access which is often flooded, toilets (WCs) which are only in the parking area, to wooden prayer rooms located above swamps are very vulnerable to use. The marketing carried out by the managers is also carried out in accordance with sharia, starting from the absence of any element of usury in the marketing, in all aspects it is carried out without coercion (consensual), free from defective goods and also free from false promotions. By implementing a sharia marketing mix, managers can increase visitors as proven by visitors who always come to visit more than once.